Program Bantuan Stimulan Perumahan Swadaya (BSPS) di Desa Sipituhuta, Kecamatan Pollung, Kabupaten Humbang Hasundutan - Tulus Lumban Gaol; Bahrum Jamil; Beltahmamero Simamora (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2023)
The Self-Help Housing Stimulant Assistance Program (BSPS) is a government initiative aimed at Low-Income Communities (MBR) facing purchasing power limitations, providing support to acquire adequate housing. This research delves into the implementation of the BSPS program conducted by the Housing and Settlement Area Service (PKP Service) in Sipituhuta Village, Pollung District, Humbang Hasundutan Regency. The study aims to identify inhibiting factors in the program's implementation. Employing the Implementation Theory by Van Meter and Varn Horn, incorporating six indicators – policy standards and objectives, resources, implementing organization characteristics, inter-organizational communication, executors' attitudes, and the socio-economic and political environment. The research follows a Descriptive method with a Qualitative approach, gathering data through observation, interviews, and documentation. Findings reveal that the BSPS Program in Sipituhuta Village is well-implemented, yet two indicators are inadequately realized, namely limited financial resources and discrepancies between the provided data and field situations. These issues hinder location transfers and cause misunderstandings between the community and the village government regarding beneficiary data.